2023
DOI: 10.1038/s41598-023-27719-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial filtering magnetic metasurface for misalignment robustness enhancement in wireless power transfer applications

Abstract: In this paper, we present the design of spatial filtering magnetic metasurfaces to overcome the efficiency decay arising in misaligned resonant inductive Wireless Power Transfer systems. At first, we describe the analytical framework for the control of currents flowing on a finite-size metasurface, avoiding classical truncation effects on the periphery and opportunely manipulating, at the same time, the spatial magnetic field distribution produced by the closely placed RF driving coil. In order to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…By correctly designing such materials, it is possible to obtain specific properties and, consequently, to manipulate the electromagnetic radiation in order to achieve improved system performance. Being extremely popular in countless electromagnetic applications, magnetic metasurfaces were specifically proved as capable to homogenize the magnetic field, leading to a better misalignment robustness in WPT systems [33]. Moreover, other studies have shown the possibility to exploit near-zero permeability in order to realize a shielding slab [34], [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…By correctly designing such materials, it is possible to obtain specific properties and, consequently, to manipulate the electromagnetic radiation in order to achieve improved system performance. Being extremely popular in countless electromagnetic applications, magnetic metasurfaces were specifically proved as capable to homogenize the magnetic field, leading to a better misalignment robustness in WPT systems [33]. Moreover, other studies have shown the possibility to exploit near-zero permeability in order to realize a shielding slab [34], [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of a uniform current distribution in the metasurface has been shown in different application fields; still referring to WPT systems (hence to specific dimensions and frequency of operation), in Lazzoni et al (2023) it is demonstrated that the unit-cell current uniformity leads to a significantly more homogenous magnetic field distribution, fundamental to improve the WPT performance in terms of robustness to misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Taking inspiration from the recent advancements in metamaterials encompassing novel materials [25][26][27], intricate structures [28][29][30][31], and equivalent theories [32,33], there has been a burgeoning research focus on bestowing EMMs with exceptional reconfigurability. At present, one prevalent way to adjust the electromagnetic properties of an EMM unit cell is to introduce external capacitance [34][35][36] (see figure 1(c)). Most research work uses adjustable capacitors [37,38], which can alter their capacitance values by mechanically rotating the rotor to change the relative area with the stator.…”
Section: Introductionmentioning
confidence: 99%